1984
DOI: 10.1113/jphysiol.1984.sp015109
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the three‐hour‐period sleep‐wakefulness cycle and growth hormone secretion in the immature rat.

Abstract: SUMMARY1. The temporal pattern of growth hormone (GH) secretion throughout a day and its correlation with the sleep-wakefulness cycle in the 29-31-day-old female rat were studied by serial blood sampling through an intracardiac cannula at 10-min intervals. Electroencephalograms (e.e.g.s) recorded continuously during blood sampling periods were scored into wakefulness and sleep, and the amount of sleep for every 10 min was plotted against the GH value as assessed by radio-immunoassay.2. By analysis of the power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…It has been confirmed in the immature rat that a 20% decrease in hemato crit did not cause singificant effects on the health or on the weight gain afterwards [ 19]. Further, this loss of blood was not to be stress ful for the rat on the basis of effects on growth hormone secretion which has been shown to be responsive to stress [20], Following a control period, during which at least 4 MUA volleys were recorded, muscimol (2 mg/kg. Sigma Chemical Co., St. Louis, Mo., USA) or bicuculline (2 mg/kg, (-)bicuculline methiodide.…”
Section: Methodsmentioning
confidence: 99%
“…It has been confirmed in the immature rat that a 20% decrease in hemato crit did not cause singificant effects on the health or on the weight gain afterwards [ 19]. Further, this loss of blood was not to be stress ful for the rat on the basis of effects on growth hormone secretion which has been shown to be responsive to stress [20], Following a control period, during which at least 4 MUA volleys were recorded, muscimol (2 mg/kg. Sigma Chemical Co., St. Louis, Mo., USA) or bicuculline (2 mg/kg, (-)bicuculline methiodide.…”
Section: Methodsmentioning
confidence: 99%
“…That is, (1) although the episodic secretion of GH is correlated with the sleep cycle [8,9], a decrease in the amount of sleep by a sleep-deprivation procedure induces only an attenua tion of GH secretion that occurs at the anticipated time in the 3-hour rhythm [10]; (2) there is a small number of ani mals in which a temporal dissociation of the three ultradian rhythms, i.e., GH, CS and sleep, is apparent [11], and (3) under the conditions of a continuous-sleep state induced by long-term thiopental anesthesia, the ultradian rhythms of GH are still maintained with almost the same periodicities as in the freely moving animals [13]. Thus, it was considered that each of the GH, CS and sleep rhythms was controlled by a separate pacemaker, although sharing the same basic rhythmicities.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrate that CS and GH secretions are able to manifest the same ultradian rhythms as those in the unanesthetized, freely moving condition even in the continuous-sleep state due to thiopental anesthesia. Combined with our previous findings, the CS, GH and sleep-wakefulness rhythms appear to be governed by separate pacemakers, although sharing the same basic ultradian rhythm.Recent experiments in our laboratory demonstrated that episodic secretion of growth hormone (GH), occurring with a 3-hour periodicity, is correlated with the 3-hour period sleep cycle in the immature and adult rat [8][9][10]. It is docu mented further that secretion of corticosterone (CS) is also episodic [2,7,15] and synchronized with locomotor activity [7,15].…”
mentioning
confidence: 99%
“…Rats and mice show ultradian rhythms of sleep coupled with GH secretion over periods of 2-4 h (Kawakami et al 1984;Kimura and Tsai 1984;Mitsugi and Kimura 1985;Tannenbaum 1987;MacLeod et al 1991). GH secretion follows sleep with a lag of about 10 min (Kawakami et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…GH secretion follows sleep with a lag of about 10 min (Kawakami et al 1984). There is also circadian rhythmicity, so that most sleep occurs during the photophase (Mitler et al 1977).…”
Section: Introductionmentioning
confidence: 99%